Vous êtes sur la page 1sur 11

# MARCELO C.

GONTIAS BSEE-1

A.
1. x+ 3 y z=4
3 x2 y+ 4 z=11

2 x + y +3 z=13

GAUSS-ELIMINATION

|]

1 3 1 4
3 2 4 11
2 1
3 13

[ |]
1 3
0 1
0 0

1 4
7 1
11 11
4 12
11 11

[ |]

1 3 1 4
R23 R01 1 7 1
11 11
R32 R1
0 1 1 1

|]

1
3 1 4
0 11 7 1
0 5
5 5

[ |]
1 3

R3R2

0 1
0 0

1
7
11
1

4
1
11
3

R
( 11
)
R
( 5 )
2

z=3

y=2

7
1
z=
11
11

x+ 3 y z=4
y=

1 7
+ (3)
11 11

x=4 +33 (2 )

x=1

GAUSS-JORDAN ELIMINATION

[ |]
1 3 1 4
0 1 0 2
0 0 1 3

7 R3
R2 +
11

( )

[ |]
1 0 1 2
0 1 0 2
0 0 1 3

[ |]

R13 R2

1 0 01
0 1 02
0 0 13

## x=1 ; y=2; z=3

2. 3 x y2 z=13
5 x+3 y z=4
2 x 7 y+ 3 z=36

GAUSS-ELIMINATION
R1
R3

( )
( R5 )
(2)
2
3

R32R11

((156 RR )
32

R1 + R3

| ]

3 1 2 13
5 3 1 4
2 7 3 36

[ |]
1
3
3
1
5
7
1
2

2
13
3
3
1
4
5
5
3
18
2

[ |] [ |]
1
3
14
0
15
19
0
6
1

2
3
7
15
13
6

13
3
77
15
41
3

1
3

0 1

2
3
1
2
13
19

13
3
11
2
82
19

## MARCELO C. GONTIAS BSEE-1

[ |] [ |]
1

1
3

2
3
1
2
45
38

13
3
11
2
45
38

1
3

R3 + R20

2 13
3 3
1 11
2
2
1
1

1
11
y + Z=
2
2
y=

z=138 R
3
45

( )

1
2
13
x y z=
3
3
3

11 1
(1)
2 2

1
2
13
x= ( 5 ) + ( 1 )
3
3
3

y=5

x=2

GAUSS-JORDAN ELIMINATION

[ |]
1 0
0 1
0 0

1
2
0
1

( RR3 )
R ( )
2

5
2
5
1

R1 +

( R2 )

[ |]

R1 +

1 0 0 2
0 1 0 5
0 0 1 1

## x=2 ; y=5 ; z=1

3.

x= y2 z

x y +2 z=0

2 y=x+ 3 z +1

x2 y+ 3 z =1

z=2 y2 x3

2 x 2 y + z=3

GAUSS-ELIMINATION

[ |] [
1 1 2 0
1 2 3 1
2 2 1 3

|]

1 1 2 0
0 1 1 1
0 0 3 3

R2R1
R32 R1

|]

1 1 2 0
0 1 1 1
0 0
1 1

yz=1

x y +2 z=0

y=1+1

x=22 ( 1 )

y=2

x=0

R 2

z=1

( 3R )
3

GAUSS-JORDAN ELIMINATION
R 2 + R3

R 1 + R2

R12 R3

[ |]
1 1 2 0
0 1 02
0 0 11

x=0 ; y=2 ; z =1

[ |]
1 0 22
0 1 02
0 0 11

[ |]
1 0 00
0 1 02
0 0 11

## MARCELO C. GONTIAS BSEE-1

B.
1.

2 5 3
Let A= 6 1 8 Find A1
9 4 7

[ ][

][ ]

a b c 2 5 3
1 0 0
d e f 6 1 8 = 0 1 0
g h i 9 4 7
0 0 1

FIRST ROW
eq .1 :2 a+6 b+ 9 c=1

eq .2 :5 ab+4 c=0

eq .3 :3 a+8 b +7 c=0

STEP 1: 6 ( eq .2 )+ eq .1

30 a6 b+24 c =0

171 a=39

## +(2 a+ 6 b+9 c=1)

a=

32 a+33 c=1

13
57

STEP 4 : Substitute a eq . 4

132 a
then, c=
(eq .4 )
33

132
c=

STEP 2: 8 ( eq .2 )+ eq .3
40 a8 b+32 c=0

c=

33
43
171

## STEP 5: Substitute ac eq .1/2/3

43 a+ 39 c=0(eq .5)
STEP 3 :Substitute eq .4 eq . 5

b=5

a
=0
( 132
33 )

b=

43 a+ 39

( 13
57 )

43
+4
( 13
57 ) ( 171 )

23
171

SECOND ROW
eq .1 :2 d+ 6e+9 f =0

eq .2 :5 de +4 f =1

eq .3 :3 d +8e+7 f =0

STEP 1: 6 ( eq .2 )+eq .1

STEP 2: 8 ( eq .2 )+ eq .3

30 d6e+24 f =6

40 d 8e+32 f =8

32 d+33 f =6

## 43 d +39 f =8(eq .5)

then, f =

632 d
(eq .4)
33

STEP 3 :Substitute eq .4 eq . 5

43 d +39

d
=8
( 632
33 )

632
f=

33

171 d=30

d=

f=

10
57

( 1057 )

2
171

## STEP 5: Substitute ac eq .1/2/3

STEP 4 : Substitute d eq . 4

e=5
e=

( 1057 )+ 4 ( 1712 )1

13
171

THIRD ROW
eq .1 :2 g+ 6 h+9 i=0

eq .2 :5 gh+ 4 i=0

## eq .3 :3 g+8 h+7 i=1

STEP 1: 6 ( eq .2 )+ eq .1

30 g6 h+ 24 i=0

171 g=33

## +(2 g+6 h+ 9i=0)

g=

32 g+33 h=0
then, h=

32 g
(eq .4)
33

STEP 2: 8 ( eq .2 )+ eq .3
40 g8 h+32i=0
+(3 g+8 h+ 7 i=1)
43 g+39 i=1(eq .5)
STEP 3 :Substitute eq .4 eq . 5

43 g+39

( 3233g )=1

11
57

STEP 4 : Substitute d eq . 4
32
i=
f=

( 1157 )

33
32
171

e=5
e=

171 )

37
171

## MARCELO C. GONTIAS BSEE-1

A1

2.

23
43
( 13
57 ) ( 171 ) ( 171 )
10
13
2
= ( ) (
57
171 ) ( 171 )
37
( 1157 ) ( 171
) (32
171 )

2
4
0
3
A
2 1

0
7

8 0
1 1
3 4

1 3

a
e

2
4
0
3

2 1

0
7

b
f
j
n

c
g
k
o

d
h
l

Find A1

8 0 1
1 1 0

3 4 0

1 3 0

0
1
0
0

0
0
1
0

0
0
0

FIRST ROW
eq .1 :4 a+0 b2 c+7 d=1
eq .3 :8 a+ b+3 c +d=0

## eq .2 :2 a+3 bc+ 0 d=0

eq .4 : 0 ab +4 c3 d=0

a=

c3 b
2

## STEP 2: Substitute ' a ' eq .12

(44 b+ 28 c+ 4 d )=0

4 ( c3 b )4 c +14 d=2

## (7 b+28 c21 d )=0

4 c12 b4 c +14 d =2

## 37 b+25 d=0 (eq . 7)

6 b+7 d=1(eq . 5)

STEP 4 :7 ( eq .7 )25( eq . 5)

8 ( c3 b )+2 b+ 6 c+ 2d =0

## 150 b175 d =25

22 b+14 c+ 2 d=0

109 b=25

11 b +7 c +d=0 (eq . 6)

STEP 3 :4 ( eq .6 )7(eq . 4)

b=

25
109

STEP 5: Substitute b eq .5

## MARCELO C. GONTIAS BSEE-1

25
( 109
)+7 d=1

763 d=109+150
d=

37
109

STEP 6 :Substitute bd eq . 6

11

25
37
+7 c +
=0
109
109

( )

763 c=27537
34
109

c=

STEP 7 :Substitute bc eq . 2

2 a+3

25
34
=0
( 109
) 109

218 a=3475
a=

41
218

SECOND ROW
eq .1 :4e+0 f 2 g+7 h=0

## eq .2 :2e+3 f g+0 h=1

eq .3 :8e+ f +3 g+h=0

eq .4 : 0ef +4 g3 h=0

## STEP 2: Substitute ' e ' eq . 23

e=

h=

2 (2 g7 h ) +12 f 4 g=4
4 g14 h+12 f 4 g=4

2 g7 h
4

22
109

STEP 5: Substitute h eq .5

22
( 109
)=2

6 f 7 h=2(eq . 5)

6 f 7

8 ( 2 g7 h ) + 4 f +12 g+ 4 h=0

654 f =218+154

## 16 g56 h+ 4 f +12 g+ 4 h=0

f +7 g13 h=0(eq . 6)

f=

62
109

STEP 3 :4 ( eq .6 )7(eq . 4)

STEP 6 : Substitute f h eq . 6

## 4 f +28 g52 h=0

62
22
+7 g13
=0
109
109

7 f 28 g +21 h=0
11 f 31 h=0 (eq . 7)

## STEP 4 :6 ( eq .7 )11 (eq . 5)

66 f 186 h=0

66 f +77 h=22
109 h=22

( )

763 g=28662
g=

32
109

STEP 7 : Substitute gh eq . 1

4e-2

32
22
( 109
)+7( 109
)=0

## MARCELO C. GONTIAS BSEE-1

436 e=64154

e=

45
218

THIRD ROW
eq .1 :4 i+0 j2 k +7 l=0

eq .2 :2i+3 jk +0 l=0

eq .3 :8 i+ j+3 k +l=1

eq .4 : 0i j+4 k3 l=0

i=

k3 j
2

## STEP 2: Substitute ' i' eq .13

j=

28
109

STEP 5: Substitute j eq . 5
+7 l=0
( 28
109 )

4 ( k3 j )4 k +14 l=0
4 k12 j4 k +14 l=0

763 l=168

24
109

6 j+7 l=0( eq . 5)

l=

8 ( k 3 j ) +2 j+6 k +2 l=2

STEP 6 :Substitute jl eq . 6

## 8 k 24 j+2 j+6 k+ 2l=2

11 j+7 k +l=1(eq . 6)

11

24
+ 7 k
=1
( 28
)
109
109

STEP 3 :4 ( eq .6 )7(eq . 4)

## 44 j+28 k+4 l=4

k=

7 j28 k +21l=0

25
109

STEP 7 :Substitute jk eq . 2

37 j+ 25l=4 (eq . 7)

STEP 4 :7 ( eq .7 )25(eq . 5)
259 j+175 l=28

## 150 j175 l=0

109 j=28

2i+3

25
+
=0
( 28
)
109 109

218 i=8425

i=

59
218

FOURTH ROW
eq .1 :4 m+0 n2 o+7 p=0
eq .3 :8 m+n+3 o+ p=0

m=

o3 n
2

## eq .2 :2 m+3 no+ 0 p=0

eq .4 : 0 mn+4 o3 p=1

## MARCELO C. GONTIAS BSEE-1

4 ( o3 n )4 o+14 p=0

STEP 5: Substitute n eq .5

## 6 n+7 p=0 (eq . 5)

8 ( o3 n ) +2 n+6 o+ 2 p=0

49
( 109
)+7 p=0

763 p=294

42
109

## 8 o24 n+2 n+6 o+2 p=0

p=

11 n+ 7 o+ p=0(eq .6)

STEP 6 :Substitute n p eq . 6

STEP 3 :4 ( eq .6 )7(eq . 4)

11

44 n+28 o +4 p=0

49
42
=0
( 109
)+7 o+ 109

763 o=53942

## 37 n+25 p=7(eq .7)

o=

STEP 4 :7 ( eq .7 )25(eq . 5)

71
109

STEP 7 :Substitute no eq .2

109 n=49

n=

49
109

2 m+3

49
71
=0
( 109
) 109

218 m=71147

m=

38
109